Manipulation of metabolic pathways to promote stem-like and memory T cell phenotypes for immunotherapy - Claiborne, Michael D. (Frontiers in Immunology, 2023)
Utilizing the immune system’s capacity to recognize and kill tumor cells has revolutionized cancer therapy in recent decades. Phenotypic study of antitumor T cells supports the principle that superior tumor control is achieved by cells with more long-lived memory or stem-like properties as compared to terminally differentiated effector cells. In this Mini-Review, we explore recent advances in profiling the different metabolic programs that both generate and define subsets of memory T cells. We additionally discuss new experimental approaches that aim to maximize the durability and sustained antitumor response associated with memory T cells within the unique immunosuppressive conditions of the tumor microenvironment.